Application of European guidelines for inguinal hernia in a tertiary hospital setting: Time for a change? EHS guideline adherence in hernia repair - Skafi, Khaled; Berrevoet, Frederik (Journal of Surgery and Medicine, 2025)
Background/Aim: The European Hernia Society (EHS) published practice guidelines in 2018, aiming to standardize inguinal hernia repair. These are not obligatory, and deviations in clinical practice may occur. This study investigates whether these guidelines were followed in a tertiary center and explores reasons for deviations. Methods: A retrospective cohort study was conducted on 1607 patients who underwent inguinal hernia repair at Ghent University Hospital (2007–2020). Outcomes such as complications, recurrence, and chronic pain were analyzed in relation to EHS guideline adherence. Results: TAPP was significantly associated with wound complications (OR 3.96, 95% CI 1.75–8.94; P=0.001). Lichtenstein repair showed the lowest recurrence rate (5.7%) but was often used in lower-risk patients, suggesting possible selection bias. Overall adherence to EHS guidelines was 60%. No significant difference in chronic postoperative pain was observed between open and laparoscopic techniques (P=0.21). Predictors such as age <50 years (OR 2.28), symptomatic hernias (OR 2.15), and laparoscopic repair (OR 1.39) were associated with wound complications. Conclusion: EHS guidelines provide valuable direction but are not always reflected in practice. Clinical realities such as surgeon experience, patient factors, and hospital logistics influence deviation. These findings emphasize the need for more flexible, context-sensitive guidelines, supported by further prospective studies.